Dysfunkcyjne przywództwo Jeremy’ego Corbyna (Politeja, 2022)
JEREMY CORBYN’S DYSFUNCTIONAL LEADERSHIPJeremy Corbyn’s tenure at the helm of the Labour Party was exceptional for number of reasons. He was the first Labour leader elected directly by party members and supporters. Leftwing rebel, Corbyn had not spent a single day in frontbenches during his more than three decades long parliamentary career, until he took the top spot. Elected against the wishes of party establishment, he found himself in constant opposition with the parliamentary party. This unresolvable conflict both defined and doomed his leadership. This article looks at Jeremy Corbyn’s tenure as a leader of the Labour Party as an example of a dysfunctional leadership. It tries to explain how and why it became leadership that was both ineffective and detrimental to the party